In-Service Teacher Development Policy: A Systemic Analysis of Pedagogical and Professional Competence Enhancement - Muhammad Junaidi; Titi Kadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
In-service teacher development is a strategic policy instrument for maintaining educational quality because it connects national reform priorities with classroom-level professional learning. This article analyzes the policy concept of in-service teacher development, its contribution to pedagogical and professional competence, and the implementation challenges that limit its impact in Indonesian schools. The study used a descriptive qualitative design based on library research and policy analysis. Recent international journal articles, policy-oriented studies, and empirical evidence on teacher professional development, professional learning communities, digital competence, and instructional leadership were synthesized through content analysis. The findings indicate that in-service development contributes to pedagogical competence when it strengthens reflective practice, formative assessment, differentiated instruction, and lesson-based collaboration. It contributes to professional competence when it supports content mastery, digital pedagogy, and Technological Pedagogical Content Knowledge. However, the impact is constrained by administrative formalism, unequal resources, top-down training, weak school leadership, and limited evaluation of classroom outcomes. The article recommends a systemic, collaborative, digitally supported, and impact-oriented model of teacher development.